Regulation of CD8+ T Cell Responses to Retinal Antigen by Local FoxP3+ Regulatory T Cells - McPherson, Scott W.; Heuss, Neal D.; Gregerson, Dale S. (Frontiers in Immunology, 2012)
While pathogenic CD4 T cells are well known mediators of autoimmune uveoretinitis, CD8 T cells can also be uveitogenic. Since preliminary studies indicated that C57BL/6 mice were minimally susceptible to autoimmune uveoretinitis induction by CD8 T cells, the basis of the retinal disease resistance was sought. Mice that express β-galactosidase (βgal) on a retina-specific promoter (arrβgal mice) were backcrossed to mice expressing green fluorescent protein and diphtheria toxin receptor under control of the Foxp3 promoter (Foxp3-DTR/GFP mice), and to T cell receptor transgenic mice that produce βgal specific CD8 T cells (BG1 mice). These mice were used to explore the role of regulatory T cells in the resistance to retinal autoimmune disease. Experiments with T cells from double transgenic BG1 x Foxp3-DTR/GFP mice transferred into Foxp3-DTR/GFP x arrβgal mice confirmed that the retina was well protected from attempts to induce disease by adoptive transfer of activated BG1 T cells. The successful induction of retinal disease following unilateral intraocular administration of diphtheria toxin to deplete regulatory T cells showed that the protective activity was dependent on local, toxin-sensitive regulatory T cells; the opposite, untreated eye remained disease-free. Although there were very few Foxp3+ regulatory T cells in the parenchyma of quiescent retina, and they did not accumulate in retina, their depletion by local toxin administration led to disease susceptibility. We propose that these regulatory T cells modulate the pathogenic activity of βgal-specific CD8 T cells in the retinas of arrβgal mice on a local basis, allowing immunoregulation to be responsive to local conditions.